2018
DOI: 10.1371/journal.pntd.0006774
|View full text |Cite
|
Sign up to set email alerts
|

Rutin (quercetin-3-rutinoside) modulates the hemostatic disturbances and redox imbalance induced by Bothrops jararaca snake venom in mice

Abstract: Snakebites are a major Collective Health problem worldwide. In Brazil, Bothrops jararaca snake venom (BjV) evokes hemostatic disturbances, bleeding manifestations, and redox status imbalance. Specific antivenom therapy, although efficacious to revert most snakebite-induced manifestations, is incapable of treating secondary manifestations, such as oxidative/nitrosative stress. Searching for new complementary therapies that could attenuate physiological derangements triggered by envenomation, we elected to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 65 publications
6
41
0
12
Order By: Relevance
“…We found 29 papers that used this antibody to measure human, mouse, rabbit and canine TF by a variety of methods, including 15 that used the antibody for western blotting (Table S1). 33‐61 Importantly, Abcam evaluated the ability of the antibody to detect human TF in wild‐type and KO cell lines by western blotting 62 . Based on the data they obtained, they recently withdrew ab151748 and stated that “after evaluation, using a HAP1 knockout cell line, ab151748 was not shown to react specifically with the target protein and has therefore been discontinued.” We confirmed that this antibody does not detect mouse TF by western blotting but rather a nonspecific band.…”
Section: Discussionmentioning
confidence: 99%
“…We found 29 papers that used this antibody to measure human, mouse, rabbit and canine TF by a variety of methods, including 15 that used the antibody for western blotting (Table S1). 33‐61 Importantly, Abcam evaluated the ability of the antibody to detect human TF in wild‐type and KO cell lines by western blotting 62 . Based on the data they obtained, they recently withdrew ab151748 and stated that “after evaluation, using a HAP1 knockout cell line, ab151748 was not shown to react specifically with the target protein and has therefore been discontinued.” We confirmed that this antibody does not detect mouse TF by western blotting but rather a nonspecific band.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Bothrops jararaca snake venom (BjV) evokes hemostatic disturbances, bleeding manifestations, and redox status imbalance. Sachetto et al (2018) demonstrated the modulatory activity of rutin on the hematological, hemostatic and redox status markers altered by BjV injection in mice. It was found that rutin attenuated local hemorrhage, and the increase in reactive species, prevented the fall in RBC counts and fibrinogen levels, diminished tail bleeding and shortened prothrombin time evoked by envenomation.…”
Section: Haematoprotective Propertymentioning
confidence: 95%
“…All procedures involving animals were in accordance with the National Guidelines from Conselho Nacional de Controle de Experimentação Animal (CONCEA) [34]. Blood and liver samples were collected from the same mice used previously [33].…”
Section: Ethics Statementmentioning
confidence: 99%
“…Mice from the saline control group were injected subcutaneously (s.c.) with sterile saline alone (vehicle), and mice from the BjV group were injected with freshly diluted BjV (1.6 mg/kg body weight, s.c.). The dose of BjV was based on a previous report [33], and it evoked characteristic hemostatic disturbances. After 3, 6 or 24 h, mice were anesthetized with isoflurane (induction and maintenance at 2.5%) for the collection of blood and tissues.…”
Section: Envenomationmentioning
confidence: 99%
See 1 more Smart Citation